Associations between affect and empathic accuracy during conflict interactions in couples. (June 2022) - Berlamont, Liesbet; Sels, Laura; Ickes, William; Ceulemans, Eva; Hinnekens, Céline; Verhofstadt, Lesley
The current research examined how intimate partners' affect is related, on a moment-to-moment basis, to their level of empathic accuracy during conflict interactions. To this end, we analyzed data from two laboratory-based studies ( n = 155 and n = 172 couples) in which couples participated in a conflict interaction task, followed immediately by a video-review task during which they reported on their own feelings and thoughts and inferred those of their partner at different moments in the interaction. We found that the partners' affective similarity—for both positive (Studies 1 and 2) and negative affect (Study 2)—was related to greater perceiver empathic accuracy for both the partner's feelings (Studies 1 and 2) and the partner's thoughts (Study 2). The data from Study 2 also revealed a complementary effect: lower levels of empathic accuracy for feelings at moments of affective dissimilarity between the partners (i.e., when a perceiver was feeling positive while his/her partner was feeling negative).